2012
DOI: 10.1108/14636641211254914
|View full text |Cite
|
Sign up to set email alerts
|

Prison organisational climate: exploring the impact of climate on emotional well being

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/ authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…As Lim et al (2010) explained, this might suggest that mental health professionals are likely to develop life experience with emotional maturity that serves as a coping strategy as they get older. This would also seem to support the findings of Worthington (2007Worthington ( , 2012 who suggested that length of service was related to development of more positive attitudes. According to Lim et al (2010), as mental health professionals grow older it is hypothesised that they become adept at dealing with their clients and providing treatment services; factors that they argue may contribute to higher levels of personal accomplishment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As Lim et al (2010) explained, this might suggest that mental health professionals are likely to develop life experience with emotional maturity that serves as a coping strategy as they get older. This would also seem to support the findings of Worthington (2007Worthington ( , 2012 who suggested that length of service was related to development of more positive attitudes. According to Lim et al (2010), as mental health professionals grow older it is hypothesised that they become adept at dealing with their clients and providing treatment services; factors that they argue may contribute to higher levels of personal accomplishment.…”
Section: Discussionsupporting
confidence: 86%
“…In terms of the precursory factors for burnout, some literature has suggested that organisational factors such as work hours (Ray et al, 2013), work overload (Cox, 1993;Muldary, 1983) and length of service (Worthington, 2007(Worthington, , 2012 are important predictors of burnout. However, Lim et al (2010) propose that individual attributes are also relevant in understanding of burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as privacy safety, structure, support, emotional feedback, social stimulation, activity, and freedom have all been identified as important influences here (Moos, 1968). For example, Worthington (2012) examined the influence of social climate within prisons, concluding that working in certain areas of the prison (described as ''dirty work'') was associated with lower levels of staff wellbeing and less positive interaction with prisoners. It is, however, the role that SEWB potentially plays in relation to organisational outcomes that are of most interest, particularly in relation to the good order and discipline of the prison, suicide prevention, and offender rehabilitation.…”
Section: Prisons and Sewbmentioning
confidence: 99%
“…Furthermore, exploring the role of emotional labour in a prison setting, Worthington (2007) found that prison officers engaged in emotional labour as a way of protecting themselves from the spill-over of their home life into work. According to Worthington (2012), in the same way that emotional labour may be regarded as a form of inhibiting private experiences within the workplace, the management of boundaries between work and home may also serve the same function.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ashforth et al (2000) argue that segmentation provides clear boundaries between work and home that in turn reduces blurring between roles. In forensic work, this has been highlighted as an effective approach to prevent the spill-over between work and home (Worthington, 2012). However, the transition between roles may be more difficult as a result of the psychological and physical disparity.…”
Section: Introductionmentioning
confidence: 99%